Ski-jumpers` performance in a laboratory setting: a 29-year longitudinal study - Janura, M.; Elfmark, M.; Cabell, L.; Svoboda, Z. (Journal of Sports Sciences, 2015)
This study assesses the longitudinal changes in anthropometric and motor parameters of ski jumpers. Male ski jumpers (n = 329) at various competitive levels participated in this study. These competitors were divided into two groups by age (18 years and younger, and over 18 years), and then divided into seven even intervals within those groups. Basic anthropometric parameters, maximal relative isometric knee extensor force, reaction time, knee extension time, and vertical jump height were measured. The conditions, instruments, and systems of measurement were consistent throughout the study. A reduced body mass index (BMI) in the adult jumpers was significant (P < .01) in the first three (1982-1993) and in the last three (1998-2010) intervals. Adults had an increase of maximal relative isometric knee extensor force (P < .01) in the last three intervals (1998-2010). They had greater maximal relative isometric knee extensor force (with exception of the first interval, 1982-1985) and vertical jump height than younger competitors (P < .01). Both young and adult jumpers exhibited the increase of strength and power in the lower limbs and a decrease in BMI during the whole observed period.